In Abundance: Networked Participatory Practices as Scholarship - Stewart, Bonnie E (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
In an era of knowledge abundance, scholars have the capacity to distribute and share ideas and artifacts via digital networks, yet networked scholarship often remains unrecognized within institutional spheres of influence. Using ethnographic methods including participant observation, interviews, and document analysis, this study investigates networks as sites of scholarship. Its purpose is to situate networked practices within Boyer’s (1990) four components of scholarship – discovery, integration, application, and teaching – and to explore them as a techno-cultural system of scholarship suited to an era of knowledge abundance. Not only does the paper find that networked engagement both aligns with and exceeds Boyer’s model for scholarship, it suggests that networked scholarship may enact Boyer’s initial aim of broadening scholarship itself through fostering extensive cross-disciplinary, public ties and rewarding connection, collaboration, and curation between individuals rather than roles or institutions.